2012
DOI: 10.1371/journal.pone.0040456
|View full text |Cite
|
Sign up to set email alerts
|

Use of Multiplex Allele-Specific Polymerase Chain Reaction (MAS-PCR) to Detect Multidrug-Resistant Tuberculosis in Panama

Abstract: The frequency of individual genetic mutations conferring drug resistance (DR) to Mycobacterium tuberculosis has not been studied previously in Central America, the place of origin of many immigrants to the United States. The current gold standard for detecting multidrug-resistant tuberculosis (MDR-TB) is phenotypic drug susceptibility testing (DST), which is resource-intensive and slow, leading to increased MDR-TB transmission in the community. We evaluated multiplex allele-specific poly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
20
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 29 publications
(25 citation statements)
references
References 28 publications
4
20
0
Order By: Relevance
“…As previously reported (34), all but one of the resistant strains had mutations in the RIF resistance-determining region of RpoB, which is commonly seen in other RIF-resistant strains (37). Most of the streptomycin-resistant strains had the nucleotide substitu- tion C517T (30 isolates) or A514C (1 isolate) in rrs (the 16S rRNA), 5 isolates had K43R or K88R mutations in RpsL, and 11 isolates had nonsynonymous or frameshift mutations in GidB (38-40) (see Table S1 in the supplemental material).…”
Section: Multidrug-resistant Tuberculosis In Panamasupporting
confidence: 72%
See 3 more Smart Citations
“…As previously reported (34), all but one of the resistant strains had mutations in the RIF resistance-determining region of RpoB, which is commonly seen in other RIF-resistant strains (37). Most of the streptomycin-resistant strains had the nucleotide substitu- tion C517T (30 isolates) or A514C (1 isolate) in rrs (the 16S rRNA), 5 isolates had K43R or K88R mutations in RpsL, and 11 isolates had nonsynonymous or frameshift mutations in GidB (38-40) (see Table S1 in the supplemental material).…”
Section: Multidrug-resistant Tuberculosis In Panamasupporting
confidence: 72%
“…As noted previously (34), mutations at alternative (non-S315) residues in KatG appear to explain most of the remaining INH-resistant strains (8 of 10 strains) (see Table S2 in the supplemental material), as almost no mutations were observed in other genes associated with INH resistance (35,36). The inhA promoter mutation was associated primarily with non-LAM MDR strains (8 of 14 isolates), whereas 50 of 52 LAM MDR strains had some nonsynonymous mutations in KatG (and only 3 had the inhA CϪ15T mutation).…”
Section: Multidrug-resistant Tuberculosis In Panamasupporting
confidence: 63%
See 2 more Smart Citations
“…Although it is not a commonly recognized mutation (29), Y337C has been reported to confer INH resistance among nonclustered isolates (30). Our previous studies revealed that approximately 16% of clustered MDR isolates identified in Panama over the past decade lacked mutations in the katG and inhA loci (31). The second case with discordant results involved isolate 044-04, which contained a CϪ15T mutation detected with the LPA, although an indeterminate reaction was noted with the NRA.…”
Section: Discussionmentioning
confidence: 96%